The Human Auditory Cortex - Poeppel, David; Overath, Tobias; Popper, Arthur N.; Fay, Richard R. (Springer Handbook of Auditory Research, 2012)
The auditory cortex of humans must process a remarkable amount of complex and dynamically changing acoustic information. The Human Auditory Cortex brings the Springer Handbook of Auditory Research to its first detailed examination of auditory cortex, with emphasis on the techniques available as well as some major conceptual challenges. Introduction: Why Human Auditory Cortex? David Poeppel and Tobias Overath Part I The Methods Architecture, Connectivity, and Transmitter Receptors of Human Auditory Cortex Stephanie Clarke and Patricia Morosan Invasive Research Methods Matthew A. Howard III, Kirill V. Nourski, and John F. Brugge Recording Event-Related Brain Potentials: Application to Study Auditory Perception Claude Alain and István Winkler Magnetoencephalography Srikantan Nagarajan, Rodney A. Gabriel, and Alexander Herman Hemodynamic Imaging: Functional Magnetic Resonance Imaging Thomas M. Talavage, Ingrid S. Johnsrude, and Javier Gonzalez Castillo Part II The Principal Computational Challenges Coding of Basic Acoustical and Perceptual Components of Sound in Human Auditory Cortex Deborah Hall and Daphne Barker Auditory Object Analysis Timothy D. Griffiths, Christophe Micheyl, and Tobias Overath Speech Perception from a Neurophysiological Perspective Anne-Lise Giraud and David Poeppel Cortical Processing of Music Robert J. Zatorre and Jean Mary Zarate Multisensory Role of Human Auditory Cortex Virginie van Wassenhove and Charles E. Schroeder Redefining the Functional Organization of the Planum Temporale Region: Space, Objects, and Sensory-Motor Integration Gregory Hickok and Kourosh Saberi Toward a Theory of Information Processing in Auditory Cortex Peter Cariani and Christophe Micheyl About the Editors: David Poeppel is Professor of Psychology and Neural Science in the Department of Psychology, New York University. Tobias Overath is Research Associate at The Ear Institute at University College London. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago. About the Series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.